How about the evidence assessment tools used in education and management systematic reviews? - Lan, Hui; Yu, Xuan; Wang, Zhe; Wang, Ping; Sun, Yajia; Wang, Zijun; Su, Renfeng; Wang, Ling; Zhao, Junxian; Hu, Yue; Wu, Shouyuan; Ren, Mengjuan; et al. (Frontiers in Medicine, 2023)
Objectives To systematically analyze the use of evidence assessment tools in systematic reviews of management and education. Study design and setting We systematically searched selected literature databases and websites to identify systematic reviews on management and education. We extracted general information of the included studies and information about the evidence assessment tool they applied, including whether it was used for methodological quality assessment, reporting quality assessment or evidence grading, as well as the name, reference, publication year, version and original intended use of the tool, the role of the tool in the systematic review, and whether the quality determination criteria were given. Results A total of 299 systematic reviews were included, of which only 34.8% used evidence assessment tools. A total of 66 different evidence assessment tools were used, of which Risk of Bias (ROB) and its updated version (n = 16, 15.4%) were the most frequent. The specific roles of the evidence assessment tools were reported clearly in 57 reviews, and 27 reviews used two tools. Conclusion Evidence assessment tools were seldom used in systematic reviews in social sciences. The understanding and reporting of evidence assessment tools among the researchers and users still needs improvement.